2018
DOI: 10.1186/s13640-018-0328-0
|View full text |Cite
|
Sign up to set email alerts
|

Research on the effect of image size on real-time performance of robot vision positioning

Abstract: In order to improve the real-time performance of visual positioning of the indoor mobile robot, the researchers found that the shape and size of the positioned image have a great influence on the real-time performance of the positioning calculation. In order to verify the conclusion and find the appropriate image shape and size to meet the robot's visual positioning requirements, this paper adopts four different shapes, such as quadrilateral and circular, and uses SURF algorithm to extract and recognize the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…The impact of image size on computational speeds in computer vision is demonstrated by Lyu et al. [55]. In this study, feature extraction time was tested in a real‐time visual robot which used the SURF (Speeded‐Up Robust Features) algorithm [55].…”
Section: Program Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The impact of image size on computational speeds in computer vision is demonstrated by Lyu et al. [55]. In this study, feature extraction time was tested in a real‐time visual robot which used the SURF (Speeded‐Up Robust Features) algorithm [55].…”
Section: Program Performancementioning
confidence: 99%
“…[55]. In this study, feature extraction time was tested in a real‐time visual robot which used the SURF (Speeded‐Up Robust Features) algorithm [55]. It was shown that the computation time and image size have a linearly positive relationship.…”
Section: Program Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Vision positioning systems are increasingly common in process automation [6][7][8][9][10], autonomous driving [11][12][13][14][15], or augmented reality assistants [16][17][18][19][20]. Indeed, this is one of the most promising elements in the Industry 4.0 revolution.…”
Section: Introductionmentioning
confidence: 99%
“…Los sistemas de posicionamiento por visión son cada vez más comunes en la automatización de procesos [104][105][106][107], la conducción autónoma [108][109][110][111][112], o los asistentes de realidad aumentada [113][114][115][116][117]. De hecho, este es uno de los elementos más prometedores en la revolución de la Industria 4.0.…”
Section: Capítulo 1 Introducciónunclassified